Gene networks and developmental context: the importance of understanding complex gene expression patterns in evolution. Issue 3 (9th May 2016) - Signor, Sarah A.; Arbeitman, Michelle N.; Nuzhdin, Sergey V.
SUMMARY: Animal development is the product of distinct components and interactions—genes, regulatory networks, and cells—and it exhibits emergent properties that cannot be inferred from the components in isolation. Often the focus is on the genotype‐to‐phenotype map, overlooking the process of development that turns one into the other. We propose a move toward micro‐evolutionary analysis of development, incorporating new tools that enable cell type resolution and single‐cell microscopy. Using the sex determination pathway in Drosophila to illustrate potential avenues of research, we highlight some of the questions that these emerging technologies can address. For example, they provide an unprecedented opportunity to study heterogeneity within cell populations, and the potential to add the dimension of time to gene regulatory network analysis. Challenges still remain in developing methods to analyze this data and to increase the throughput. However this line of research has the potential to bridge the gaps between previously more disparate fields, such as population genetics and development, opening up new avenues of research.